Therapeutic Efficacy of Nasoenteric Tube Feeding in Children Needing Enteral Nutrition - Chen, Mi-Chi; Chao, Hsun-Chin; Yeh, Pai-Jui; Lai, Ming-Wei; Chen, Chien-Chang (Frontiers in Pediatrics, 2021)
Background: There are limited information on therapeutic benefits and tube-related complications of pediatric naso–enteric (NE) tube feeding. We viewed from different clinical aspects of the NE tube feeding in children who intolerable naso-gastric tube feeding. Methods: A 10-year retrospective study enrolled 77 pediatric patients who underwent endoscopic-guidance NE tube placement for enteral nutrition. The evaluated data, including growth parameters, feeding volume, dependence on parenteral nutrition (PN), and nutritional markers (serum hemoglobin and albumin), were compared before and after NE tube feeding. Tube-related complications and major adverse event were also recorded. Results: A total of 77 patients (50 males) received 176 placements of endoscopic-guidance NE tube with an average duration of 133.7 (6.0–1847.3) days. The gastroesophageal reflux disease -related symptoms (vomiting, desaturations, aspiration pneumonia) improved in 71.4% patients. Feeding volume increased significantly after intervention, especially in the patients with delayed gastric emptying group, from 144.8±28.5mL/day to 1103.1±524.7mL/day (p < 0.001). Weaning from PN successfully achieved in 84.3% patients with average 9.33 ± 7.30 days. Sixteen patients (20.8%) subsequently tolerated oral feeding well after NE tube placement for an average of 24.7 ± 14.1 days. Patients without neurologic dysfunction or not ventilator-dependent status had higher chance shifting to oral feeding. Weight-for-age z-scores increased 0.15 ± 1.33 after NE tube intervention. One NE tube-related adverse event, which caused bowel perforation after insertion for 6 days, was recorded. No direct tube-related mortality was observed. Conclusions: Endoscopic-guidance NE tube placement is a relatively safe, non-invasive procedure for pediatric patients requiring enteral nutrition. NE tube feeding shows beneficial effects on symptoms improvement, PN weaning, and maintenance of body growth without major tube-related complications.